Design and optimization of alLow-voltage shunt capacitive RF-MEMS switch - Ma, Li Ya; Soin, Norhayati; Nordin, Anis Nurashikin (2014)
This paper presents the design, optimization and simulation of a radio frequency (RF) micro-electromechanical system (MEMS) switch. The device is a capacitive shunt- connection switch, which uses four folded beams to support a big membrane above the signal transmission line. Another four straight beams provide the bias voltage. The switch is designed in 0.35μm complementary metal oxide semiconductor (CMOS) process and is electrostatically actuated by a low pull-in voltage of 2.9V. Taguchi Method is employed to optimize the geometric parameters of the beams, in order to obtain a low spring constant and a robust design. The pull-in voltage, vertical displacement, and maximum von Mises stress distribution was simulated using finite element modeling (FEM) simulation – IntelliSuite v8.7® software. With Pareto ANOVA technique, the percentage contribution of each geometric parameter to the spring constant and stress distribution was calculated; and then the optimized parameters were got as t=0.877μm, w=4μm, L1=40μm, L2=50μm and L3=70μm. RF performance of the switch was simulated by AWR Design Environment 10® and yielded isolation and insertion loss of -23dB and -9.2dB respectively at 55GHz.